Never Going Back: Lessons To Carry Forward In Online Instruction - Howard Pitler; Amanda Lickteig; Seth Lickteig (The Advocate, 2023)
Research has long demonstrated that students thrive best in an online learning community when some basic tenants are followed. These tenants include establishing a peer community, module supports, studying while balancing life commitments, confidence, and the approach to learning (Farrell & Brunton, 2020; Kahn, Egbue, Palkie, & Madden, 2017; Dixson, 2010). Cultivating active engagement in online communities is a purposeful and deliberate practice that requires educators to bring together an assortment of innovative instructional techniques to foster the establishment of Communities of Practice (COP). Wenger, Trayner, and de Laat (2011) define a CoP as a “learning partnership among people who find it useful to learn from and with each other about a particular domain” (p.9). At the start of the COVID-19 pandemic, the unexpected shift to online learning in schools at all levels caused schools of education to engage in “stop-gap” measures as they worked to move quality face-to-face instruction to online learning platforms so to allow students to continue their educational pathways. By contrast, the graduate programs in Curriculum & Instruction and Educational Administration at a small Midwestern University have been fully online for nearly two decades. While course delivery has naturally evolved during that time, past experiences allowed faculty to maneuver the pandemic and online learning seamlessly. This paper will explore what works well and should be carried forward in online teaching and learning.
Keywords: online teaching and learning; communities of practice; COVID-19; teacher educators